A disposable bedpan system using an improved disposal unit and self-supporting bedpans - Gibson, G. L. (1973)
A system using totally disposable self-supporting bedpans requiring no carrier was examined in use in two hospitals. The bedpans and their contents were disposed of by destruction and flushing to waste carried out in a modified Haigh Sluicemaster disposal unit. This incorporates a positively closing and locking lid with refinements to avoid the lid slamming and has effective safety devices. The new bedpans and the improved disposal units reduce the risk of transfer and dispersal of pathogenic organisms to an acceptable level in ward and sluice room.